Analisis Kinerja Pln Berdasarkan Budaya Organisasi, Komitmen Organisasi Dan Akuntabilitas Publik (Studi Empiris Pada PT. PLN (Persero) Area Surakarta) - Ambarsari, Fitria Nova, Erma Setiawati, Dr., Akt., M.M (2015)
This study aims to analyze the performance of PT. PLN (Persero) based on organizational culture, organizational commitment and public accountability in Surakarta. Based on the results of the study are expected to provide an overview of the dynamics that occur in the PT. PLN (Persero), especially employees in carrying out their duties. This study was included in the quantitative research by using direct survey through questionnaires. The population in this study are the employees who work in PT. PLN (partners) in Surakarta. Techniques used in sampling is disproportionate stratified random sampling. Collecting data using questionnaires that have been tested for validity and reliability levels. Data were analyzed using multiple regression test, F test, test the coefficient of determination R2, and t test. The results showed that: (1) organizational culture influence the performance, from the t test obtained t for 5.351> 0.000 ttabel2,021 and significance value <0.05. (2) organizations commitment to performance, evident from the t test results obtained thitung 4,089> ttabel2,021 and significance 0.000 <0.05. (3) public accountability affect the quality of the audit, the results obtained t t test of 2.174> ttabel2,021dan significance of 0.035 <0.05. Keywords: organizational culture, organizational commitment, public accountability and organizational performance.